KONSEP MANUSIA, POTENSI PENDIDIKAN DAN MANAJEMEN DALAM PERSPEKTIF HADIS NABI MUHAMMAD SAW - F Ramdhan, Dadan; Corina Dwi C. N. J; Ita Juwita; Zasiyah Auliyatulloh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore human theory, potential, and management from the perspective of Hadith. This journal uses a qualitative approach with a literature review method. Humans are the most noble creatures created by Allah compared to other creatures. Every human being certainly has their own potential or strengths. Potential can support every educational process, as education is one of the fundamental aspects of human life that plays a crucial role in shaping character, developing potential, and preparing future generations. In the Islamic perspective, education is not just a process of transferring knowledge, but a holistic process that encompasses the development of the spiritual, intellectual, emotional, and social aspects of humans. This study will discuss the concepts of human nature, educational potential, and management in depth, analyzed from the perspective of the Hadith of Prophet Muhammad (PBUH).